Compact low-noise GeV-scale electron-positron pair spectrometer - Jaehyun Song; Youhwan Noh; Mohammad Mirzaie; Calin Ioan Hojbota; Hyeong-il Kim; Seongmin Lee; Junho Won; Chiwan Song; Woosuk Bang (Results in Physics)
Recent studies have successfully demonstrated a high-flux GeV-scale gamma-ray spectrometer using energy spectra of electron–positron pairs generated in a high-Z converter. In a confined space of a meter, resolving GeV-scale pair particles using a permanent magnet is challenging owing to its relatively weak magnetic field strength of around 1 T. In this study, we present a compact low-background GeV-scale electron–positron pair spectrometer design, utilizing permanent magnets and imaging plates, and its experimental validation. We investigated the arrangement of magnet blocks using Geant4 simulations to enhance energy resolution over a wide spectral range from MeV to GeV. An asymmetrical yoke design was implemented to maximize the bending power without obstructing particle trajectories. We utilized and evaluated the pair spectrometer system in pair-production experiments using a multi-petawatt laser, successfully detecting GeV-range electron–positron pair particles. Additional Geant4 simulations were conducted to validate the spectrometer’s performance. This research contributes to the advancement of experimental capabilities in particle physics, especially for gamma-ray spectrometers in space-constrained environments.